On Type 1 Active Galactic Nuclei with Double-peaked [O iii]. II. Properties of Long-term Optical Variability - Qi Zheng; Xingyu Zhu; Xueguang Zhang; Qirong Yuan (The Astrophysical Journal)
Double-peaked [O iii ] profiles could potentially indicate kiloparsec-scale dual active galactic nuclei (AGNs). We analyze long-term optical light curves of 35 type 1 AGNs with such features from our recent catalog in Zheng et al. These light curves are obtained from the Catalina Sky Survey and modeled using a damped random walk process. A control sample of 210 normal type 1 AGNs, matched in redshift, intrinsic luminosity, and black hole mass, is also studied. If the double-peaked [O iii ] is caused by two type 1 AGNs (dual type 1 AGN), then the combined variability from the two AGNs would be expected to differ from that of a single type 1 AGN. However, there is no statistically significant difference in the variability timescale τ and intrinsic variability amplitude σ between these double-peaked AGNs and the control sample of 210 normal type 1 AGNs. Crucially, computer simulations reveal that dual AGN systems systematically produce lower variability amplitudes than single AGNs, which is inconsistent with the observed variability properties of our double-peaked [O iii ] sample. Moreover, simulations suggest that the fraction of dual type 1 AGNs is ∼3%, indicating that double-peaked [O iii ] may not be a reliable indicator of dual type 1 AGNs in these systems. However, this does not rule out the possibility that some objects may still host dual AGNs involving other combinations, such as type 1+type 2 AGNs. Future studies with larger samples and higher-quality light curves will help clarify the true nature of these systems.